The problems of interpreter's mistake while simultaneous interpreting of political leader's speech (Zien Journal of Social Sciences and Humanities, 2023)
This article delves into the challenges faced by interpreters while conducting simultaneous interpretation of political leader's speeches. It examines the potential consequences of mistakes and their implications on communication and diplomacy.